ANALISIS PERSAMAAN SIMULTAN INSIDER OWNERSHIP, KEBIJAKAN HUTANG DAN DIVIDEN DALAM PERILAKU OPORTUNISTIK MANAGERIAL (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2009-2011) - Supriyatin, Dwi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
The research analizing the relationship between insider ownership, debt policy and dividend policy in managerial opportunistic behaviour. This research is based on the previous research by Jensen (1992). Fixed asset, Risk, Size, Growth, and Profit is used as determined variables (exogenous variables).This research focused on manufacturing companies listed in Indonesia Stock Exchange for periode 2009-2011. The method of data collecting is pooling method and result 7 firm observation. The statistical method used by this research is two stage least square regression.The result of this research shows that the proposition that financial decision and level of insider ownership are interdependent. Specifically, the level of insider ownership has a negative influence on a firm’s debt and dividen levels.